2016
DOI: 10.1103/physrevx.6.041020
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Magnitude of ‘Designer’ Spin-Orbit Interaction in Graphene on Semiconducting Transition Metal Dichalcogenides

Abstract: We use a combination of experimental techniques to demonstrate a general occurrence of spin-orbit interaction (SOI) in graphene on transition metal dichalcogenide (TMD) substrates. Our measurements indicate that SOI is ultra-strong and extremely robust, despite it being merely interfaciallyinduced, with neither graphene nor the TMD substrates changing their structure. This is found to be the case irrespective of the TMD material used, of the transport regime, of the carrier type in the graphene band, and of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
258
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(283 citation statements)
references
References 60 publications
(96 reference statements)
19
258
3
1
Order By: Relevance
“…1 shows that all graphene/TMDC heterostructures possess non-zero spin Hall conductivity, which is consistent with previous experimental results. 22 Additionally, we find that the graphene/WS 2 heterostructure stands out as the most promising for large spin Hall angles. In the inset of Although σ z (0) xy can be used as a starting point to determine the potential for spin Hall effects in these heterostructures, one also needs to consider the effect of disorder to correctly compute the spin Hall angle.…”
Section: Resultsmentioning
confidence: 74%
“…1 shows that all graphene/TMDC heterostructures possess non-zero spin Hall conductivity, which is consistent with previous experimental results. 22 Additionally, we find that the graphene/WS 2 heterostructure stands out as the most promising for large spin Hall angles. In the inset of Although σ z (0) xy can be used as a starting point to determine the potential for spin Hall effects in these heterostructures, one also needs to consider the effect of disorder to correctly compute the spin Hall angle.…”
Section: Resultsmentioning
confidence: 74%
“…To advance towards spin manipulation, recent work has focused on heterostructures of graphene and magnetic insulators [12][13][14][15][16] or strong SOC materials such as transition metal dichalcogenides (TMDCs) and topological insulators [17][18][19]. The SOC induced in graphene by a TMDC could enable phenomena such as topological edge states [20] or the spin Hall effect [21][22][23].To this end, a variety of recent experiments have explored spin transport in graphene/TMDC heterostructures [21,[24][25][26][27][28][29]. Magnetotransport measurements revealed that graphene in contact with WS 2 exhibits a large weak antilocalization (WAL) peak, revealing a strong SOC induced by proximity effects [24][25][26]30].…”
mentioning
confidence: 99%
“…To this end, a variety of recent experiments have explored spin transport in graphene/TMDC heterostructures [21,[24][25][26][27][28][29]. Magnetotransport measurements revealed that graphene in contact with WS 2 exhibits a large weak antilocalization (WAL) peak, revealing a strong SOC induced by proximity effects [24][25][26]30].…”
mentioning
confidence: 99%
See 2 more Smart Citations